Pengaruh Edukasi Gaya Hidup Sehat terhadap Pencegahan Dini Hipertensi pada Remaja - Suratun Suratun; Ni Luh Putu Ekarini; Mamah Sumartini (Jurnal Keperawatan, 2018)
Hypertension is a condition of systolic pressure above 140 mmHg and diastolic pressure above 90 mmHg. Hypertension can be prevented by controlling a healthy lifestyle including sleep habits, eating habits, weight control, not smoking or drinking alcoholic beverages, exercising regularly and skillfully in managing stress. Efforts to control a healthy lifestyle by providing education. This study aims to determine the effect of healthy lifestyle education on early prevention of hypertension in adolescents. The study design used a quasi experiment pre-post test with control group. The study sample in the intervention group and the control group were 68 respondents. The sampling technique is by purposive sampling. The results showed that the respondents were on average 15 years old and most of the respondents were male in both the intervention group and the control group. Most respondents in the intervention group did not have a family history of hypertension, while in the control group most of the respondents had a history of hypertension from father or mother. There were significant differences in educating healthy lifestyles on changes in systolic and diastolic blood pressure in the intervention group, whereas in the control group there were no significant differences.